Relationship between diabetic retinopathy and diabetic nephropathy; A longitudinal follow-up study from a tertiary care unit of Karachi, Pakistan. Issue 6 (November 2020) - Butt, Anum; Mustafa, Nida; Fawwad, Asher; Askari, Saima; Haque, Muhammad Saiful; Tahir, Bilal; Basit, Abdul
Abstract: Objective: To determine the development and progression of diabetic retinopathy in subjects with diabetic nephropathy. Methodology: This retrospective longitudinal follow up study was conducted in outpatient department of Baqai Institute of Diabetology and Endocrinology (BIDE), a tertiary care diabetes unit of Karachi Pakistan, from January 2005 to December 2016. Type 2 diabetic subjects with newly diagnosed diabetic nephropathy (DN) and sex-age matched controls were identified from the electronic database of the institute, Health Management System (HMS). Subjects with type 1 diabetes, gestational diabetes and subjects with diabetic retinopathy (DR) at the baseline of both DN and non-DN group were excluded from the study. Statistical analyses were conducted by using SPSS version 20. Result: Out of 3056 type 2 diabetic subjects, 2389 were with DN and 667 were without DN. The incidence of retinopathy was found to be 21.7 per 1000 person years. The incidence rate ratio (IRR) of 2.57 (1.92–3.43) showed that retinopathy was significantly higher in subjects with DN as compared to subjects without DN. Kaplan-Meier survival plot confirmed that subjects with DN had a worse diabetic retinopathy-free survival than subjects without DN. Conclusion: Diabetic nephropathy is an independent risk factor for the development and progression of diabetic retinopathy. Highlights: Incidence of diabetic retinopathy was found to be 21.7 per 1000 person-years. T2DM subjects with DN showed nearly 2.8 folds higher risk of diabetic retinopathy relative to subjects without DN. In non-DN group, incidence of DR is significantly higher in subjects with hypertension and long duration of diabetes. Subjects with DN had a worse diabetic retinopathy-free survival than subjects without DN.